Cost Benefit Analysis for Coal Steam Power Plants in Energy Security Framework - Fernando, Yudha; Runturambi, Arthur Josias Simon (Graduate Program Magister Manajemen Pendidikan, 2024)
Indonesia’s energy security can be assessed using a four-pronged management approach: affordability, accessibility, availability, and acceptability. This aspect is influenced by various internal and external strategic environments, such as energy supply and demand trends, investment in supporting infrastructure development, and the impact of related and cross-sectoral policies and regulations. This study based on descriptive quantitative method with a cost-benefit analysis tool of sufficient coal supplies to coal steam power plants to meet supply quality and low-cost fuel-based electricity. Besides that, this study also uses PEST (Politics, Economy, Social, Technology) analysis to look at it from the external environment. The study used secondary data using cost-effectiveness analysis tools. In addition, Focus Group Discussion was conducted to identify variable indicators that can be used to analyze alternatives and interventions. FGD’s are also conducted to assess the recognition of each variable index. The assessment uses the Likert scale. A limitation of this study is that it is a short-term effort, so the cost-benefit analysis is limited to identifying alternatives and interventions being analyzed. The results of this study are an analysis of the economic value of coal as a fuel for steam power plants as a booster of the economy in Indonesia because it can produce a lot of strong and stable electricity with inexpensive infrastructure investment. The limitation of this research is the efficiency of alternatives in analyzing the cost benefits of coal as a fuel for steam power plants.